Sex differences in risk of developing Type 2 Diabetes Mellitus (T2DM): A feasibility assessment of FINDRISC scoring and barriers to disease management in a low-income settlement of Rawalpindi, Pakistan. - Taimoor Ahmad; Aisha Tauqir; Heena Tariq; Asra Qureshi; Shirin Jalaluddin; Unab I Khan; Naaznin Lokhandwala; Adnan Ahmad Khan; Ayesha Khan (PLOS Global Public Health)
Type 2 Diabetes Mellitus (T2DM) is a growing global public health concern, especially in Pakistan where an estimated 33 million people (aged 20-79 years) have diabetes. This pilot study explores T2DM risk using FINDRISC scoring, and examines participants' knowledge, attitudes, and costs of care related to T2DM across sexes.Adult participants (aged 25-65 years) residing in a low-income neighborhood in Rawalpindi, Pakistan were selected using multi-stage cluster sampling. Data was collected via SurveyCTO® software-based questionnaire, incorporating the standardized FINDRISC tool and questions assessing diabetes-related knowledge, management practices, and the costs associated with disease management. Standardized anthropometric measurements were obtained for all individuals. Descriptive analysis, cross tabulations by sexes, Chi-square, and Fisher Exact probability tests were performed using Stata 17. The study included 260 participants (84 men, 176 women) with a mean age of 41 ± 11.8 years. Anthropometric measures revealed obesity in 44% and elevated waist circumference in 45% of men and 83% of women. Based on FINDRISC scoring, 9 (13%) men and 30 (30%) women exhibited a high risk of developing T2DM (p < 0.01). Despite demonstrating higher knowledge and positive self-management practices towards diabetes, a higher proportion of women were classified as high and very high risk of developing T2DM compared to men (30% vs 13%, p < 0.01). Among self-reported cases of T2DM (49 participants), only 63% reported paying for their treatment, with women reporting higher average monthly expenditures than men, though differences were not statistically significant. Hence, despite higher knowledge and positive self-management practice toward diabetes, women are at greater risk of developing T2DM. The findings suggest the need for expanded community testing using the FINDRISC tool T2DM risk assessment in low-income settings and linking high-risk individuals to healthcare providers. Additionally, targeted health awareness campaigns among poor urban residents, particularly addressing socio-cultural barriers that increase T2DM risk among women, are recommended.